New ways in critical management and organization studies: Honneth and the method of normative reconstruction - Visser, Max (Frontiers in Sociology, 2025)
While current global ecological, social and cultural challenges and the role of organizations therein call for involvement of critical management studies, critical scholars have been divided over how to engage with organizational practice and practitioners. In order to move this issue forward, the purpose of this paper is to propose a new approach to critical analysis in the form of the method of normative reconstruction of the Frankfurt social philosopher Axel Honneth. Toward that purpose, the basic tenets of this method of normative reconstruction are discussed and empirically illustrated through two cases, while the paper ends with conclusions and discussion.